Al-Shaykh ‘Alī Ma’sūm ‘Alim Nahḍat al-‘Ulamā’ Dhū al-Ittijah al-Ḥadīth - Subhan, Arief (Studia Islamika, 1999)
K.H. Ali Maksum is recognized as one of the most leading 'ulama's (Muslim Scholars) of Nahdlatul Ulama (NU), the biggest traditional Muslim organization in Indonesia. This can be seen not only frorn the fact the he became rais 'am (the highest post in the structure of NU) from 1981 to 1984, but also from an important political role be played in this organization. It was Ali Maksum who supported the NU to take the principle (khittah) of 1925 in 1984 by which NU come back to be a social-religious organization after having had involved in the political practice. Likewise it was also Ali Maksum who "protected" Abdurrahman Wahid -the executive head of NU- from strong criticism of the 'ulami's as advocated by K.H. As'ad Syamsul Arifin. Abdurrahman Wahid was contended from his misconduct, especially from traditional Islamic viewpoint, so that be was elected again in 1989 as the executive head of the NU.DOI: 10.15408/sdi.v6i3.725